2018
DOI: 10.2337/dc18-1236
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and Microvascular Complications: Results From the Canadian Study of Longevity in Type 1 Diabetes

Abstract: Type 1 diabetes carries a significant risk for cardiovascular mortality, but it is unclear how atherosclerosis associates with microvascular complications. We aimed to determine the relationships between atherosclerotic burden and neuropathy, retinopathy, and diabetic kidney disease (DKD) in adults with a ‡50-year history of type 1 diabetes. RESEARCH DESIGN AND METHODS Adults with type 1 diabetes (n = 69) underwent coronary artery calcification (CAC) volume scoring by wide-volume computerized tomography. Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 41 publications
(41 reference statements)
0
27
1
Order By: Relevance
“…42 Considerable coronary artery calci cation in adults with chronic type 1 DM was associated with retinopathy. 43 Our study, however, showed that these macrovascular diseases were inversely related to the risk of DR. Several explanations are possible. First, positive correlations are more frequently reported than negative ones.…”
Section: Discussioncontrasting
confidence: 57%
“…42 Considerable coronary artery calci cation in adults with chronic type 1 DM was associated with retinopathy. 43 Our study, however, showed that these macrovascular diseases were inversely related to the risk of DR. Several explanations are possible. First, positive correlations are more frequently reported than negative ones.…”
Section: Discussioncontrasting
confidence: 57%
“…Older age and male sex have also been demonstrated to be associated with in-hospital death of COVID-19 patients (3,12). Thus, to adjust age and sex, an age-(62 years) and sex-matched COVID-19 patient without diabetes was randomly selected for each patient with diabetes according to previously reported similar methods (13,14). Whenever more than one patient was available for each patient with diabetes, the match was randomly selected from those available.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, although CAC is a proxy for the burden of subclinical atherosclerosis, it may not fully reflect the underlying burden of soft plaque. Nevertheless, CAC has predicted future cardiovascular events and adverse outcomes in a number of populations ( 33 , 34 ), including people with type 1 diabetes ( 5 , 6 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 diabetes is associated with an increased risk of CVD; adults with type 1 diabetes have more coronary artery calcium (CAC) than adults without diabetes ( 3 ), which in turn predicts higher rates of incident CVD and diabetes complications ( 4 6 ). The increase in cardiovascular risk differs by sex: women with type 1 diabetes see a greater increase in CAC and their overall cardiovascular risk than do men with type 1 diabetes ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%